Falling back : incarceration and transitions to adulthood among urban youth - Fader, Jamie J. (Critical issues in crime and society., 2013)
"Jamie J. Fader documents the transition to adulthood for a particularly vulnerable population: young inner-city men of color who have, by the age of eighteen, already been imprisoned. How, she asks, do such precariously situated youth become adult men? What are the sources of change in their lives? Fallingng Back is based on over three years of ethnographic research with black and Latino males on the cusp of adulthood and incarcerated at a rural reform school designed to address 'criminal thinking errors' among juvenile drug offenders. Fader observed these young men as they transitioned back to their urban Philadelphia neighborhoods, resuming their daily lives and struggling to adopt adult masculine roles. This in-depth ethnographic approach allowed her to portray the complexities of human decision-making as these men strove to 'fall back, ' or avoid reoffending, and become productive adults. Her work makes a unique contribution to sociological understandings of the transitions to adulthood, urban social inequality, prisoner reentry, and desistance from offending"--Publisher's website.